Soft porous foaming body polishing layer, polishing pad containing soft porous foaming body polishing layer and application of soft porous foaming body polishing layer and polishing pad containing soft porous foaming body polishing layer

By controlling the density and recovery rate of the polishing layer, the structural deformation and SLURRY efficiency of soft polishing cushions under high temperature and long -term stress have solved the problem of decline in the efficiency of SLURRY, and realized the extension and reduction of the service life of the polishing pad.

CN119369313AActive Publication Date: 2025-01-28WANHUA CHEM GRP ELECTRONIC MATERIALS CO LTD +1

Patent Information

Application Number
CN202411700028.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

During use, existing soft polishing pads are prone to deformation of the hole structure due to high temperature and long-term stress, the Slurry storage and pumping efficiency decreases, the polishing performance decreases, the service life is shortened, and the cost of use is increased.

Method used

By controlling the density of the polishing layer and the 40 -hour recovery rate at a 40 -hour force of 18kPa at 50 ° C, ensure that the polishing layer has better flexible response under high temperature and long -term stress to ensure the pumping efficiency of Slurry.

Benefits of technology

Effectively extend the service life of polishing pads, reduce the cost of use, and maintain the stability of polishing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369313A_ABST
    Figure CN119369313A_ABST
Patent Text Reader

Abstract

The invention provides a soft porous foaming body polishing layer, a polishing pad containing the same and application, the surface of the polishing layer is subjected to sanding treatment and groove pressing, the density of the polishing layer is larger than or equal to 0.20 g / cm < 3 > and smaller than or equal to 0.23 g / cm < 3 >, and the 40-hour recovery rate under the action force of 18 Kpa at the temperature of 50 DEG C is larger than 90%. The chemical mechanical polishing pad comprises the soft porous foaming body polishing layer, and is sequentially connected with a middle supporting layer and a back adhesive release layer through adhesive layers. The service life of the polishing pad can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a soft porous foam polishing layer and a polishing pad containing the same and applications thereof. Background Art

[0002] Chemical Mechanical Polishing (CMP) is a process that combines the grinding action of nano-particles with the chemical corrosion action of the polishing liquid to flatten the surface of the workpiece being polished on the polishing pad. Chemical Mechanical Polishing has been widely used in the flattening process of semiconductor wafers and is an essential process in the production of wafers used to manufacture electronic components.

[0003] As a key consumable in the chemical mechanical polishing process, soft polishing pads are usually used for finishing or final polishing to achieve a lower defect rate on the polishing material.

[0004] At present, the adjustment of soft polishing pads is mostly focused on the adjustment of the pore shape in order to improve the polishing rate, such as patent CN102029577A provides a polishing pad with a double-pore structure, patent CN113524026A provides an offset porous polishing pad, etc. However, for soft polishing pads, as the grinding process proceeds during use, the surface temperature of the polishing pad will increase, and under the effect of long-term pressure, the pad base is prone to deformation, the pore structure is squeezed, and the storage and pumping efficiency of the slurry is reduced, resulting in a decrease in polishing performance and a shortened service life of the polishing pad. Frequent replacement of the polishing pad increases the cost of use. Summary of the invention

[0005] The inventors of the present invention unexpectedly discovered that by controlling the density of the polishing layer and the 40-hour recovery rate under a force of 18KPa within a certain range, it is possible to ensure sufficient Slurry storage during the polishing process, while ensuring that the structure of the polishing layer substrate is stable so that it has better elastic recovery under high temperature and long-term stress, thereby ensuring the pumping efficiency of the Slurry, effectively extending the service life of the polishing pad, and reducing the cost of use, thereby completing the present invention.

[0006] An object of the present invention is to provide a soft porous foam polishing layer having a specific polishing layer density and a 40-hour recovery rate at 50° C. and a force of 18 KPa.

[0007] Another object of the present invention is to provide a polishing pad comprising such a soft porous foam polishing layer.

[0008] Another object of the present invention is to provide application of the polishing pad in chemical mechanical polishing.

[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0010] A soft porous foam polishing layer, the density of the polishing layer is greater than or equal to 0.20g / cm 3 , less than or equal to 0.23g / cm 3 , and the recovery rate is >90% at 50℃ and 18KPa for 40 hours.

[0011] In a specific embodiment, the polishing layer material is a mixture of one or more of polyurethane resin, polyvinyl chloride resin, and epoxy resin, preferably polyurethane resin. Preferably, the 100% modulus of the polyurethane resin is 4 to 9 MPa, preferably 5 to 8 MPa, and the elongation at break of the polyurethane resin is 400 to 700%, preferably 500 to 600%.

[0012] In a preferred embodiment, the recovery rate of the polishing layer at 50° C. and 18 KPa force for 40 hours is greater than 95%.

[0013] In a specific embodiment, the polishing layer is prepared by a non-solvent phase inversion method.

[0014] In a specific embodiment, the method of non-solvent phase conversion comprises the following steps:

[0015] i) preparing a uniform coating slurry with resin, additives and solvent;

[0016] ii) uniformly coating the coating slurry on the support layer and solidifying and forming the coating slurry in a coagulation bath;

[0017] iii) Wash and dry.

[0018] On the other hand, a chemical mechanical polishing pad includes the aforementioned soft porous foam polishing layer, the polishing layer is surface-sanded and grooved, and is sequentially connected to an intermediate support layer and a back adhesive release layer through an adhesive layer.

[0019] In a specific embodiment, the intermediate support layer material comprises any one of a textile material, a non-woven material, and a hard film material; the adhesive release layer is a double-sided adhesive material with a release paper.

[0020] In yet another aspect, the chemical mechanical polishing pad is used in chemical mechanical polishing.

[0021] Compared with the prior art, the polishing layer and chemical mechanical polishing pad of the present invention have the following beneficial effects:

[0022] The polishing layer prepared by the method of the present invention has a moderate density, which can ensure sufficient slurry storage during the polishing process. On the other hand, it ensures the structural stability of the polishing layer substrate, so that it has better elastic recovery under high temperature and long-term stress, effectively prolonging the service life of the polishing pad and reducing the cost of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The figure is a comparison chart of the removal rates of the polishing pads of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0024] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0025] A chemical mechanical polishing pad comprises a soft porous foam polishing layer, the surface of the polishing layer is sanded and grooved, 0.20g / cm 3 ≤Polishing layer density≤0.23g / cm 3 , and the recovery rate is greater than 90% at 50°C and 18Kpa for 40 hours; the polishing layer is connected to the middle support layer and the back adhesive release layer in sequence through the adhesive layer to obtain a chemical mechanical polishing pad.

[0026] Specifically, the polishing layer material is a mixture of one or more of polyurethane resin, polyvinyl chloride resin, and epoxy resin, preferably polyurethane resin, more preferably wet polyurethane resin; the solid content of the wet polyurethane resin is not particularly limited, for example, the general solid content is 30%. Preferably, the 100% modulus of the wet polyurethane resin used in the present invention is 4-9MPa, wherein the 100% modulus can also be referred to as 100% mold or 100% modulus, which have the same meaning in the present invention, for example, including but not limited to 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, preferably 5-8Mpa. The elongation at break of the polyurethane resin is 400-700%, for example, including but not limited to 400%, 500%, 600%, 700%, preferably 500-600%.

[0027] Specifically, the polishing layer is prepared by a non-solvent phase conversion method, specifically, by coating a polyurethane resin coating slurry on a support layer with a certain thickness, curing and forming in a coagulation bath, washing and drying to obtain a polishing layer. The density of the polishing layer can be adjusted by adjusting the formula and process, for example, adjusting the composition of the polyurethane coating slurry, such as adding a suitable surfactant, such as anionic, non-ionic, etc., but not limited to this; for example, adjusting the coagulation bath concentration and temperature, etc., the coagulation bath preferably contains an aqueous solution of DMF, the mass concentration is 10-16%, for example, including but not limited to 10%, 11%, 12%, 13%, 14%, 15%, 16%, preferably 12-15%; the coagulation bath temperature is 20-25°C, for example, including but not limited to 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, preferably 22-24°C, preferably 0.20g / cm 3 ≤Polishing layer density≤0.23g / cm 3 , for example, including but not limited to 0.20g / cm 3 , 0.21g / cm 3 , 0.22g / cm 3 , 0.23g / cm 3 etc.

[0028] Specifically, the polishing layer is pressurized at 50°C with a force of 18KPa. The applied pressure is removed every 2 hours, and the thickness recovery after 5s and 10s of the pressure removal is recorded. The ratio of the thickness recovery after 10s to the thickness reduction due to pressurization is recorded as the recovery rate. The average recovery rate is recorded over a total of 40 hours. Preferably, the average recovery rate is greater than 90%, for example, including but not limited to 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc., and more preferably greater than 95%.

[0029] Specifically, the surface of the polishing layer is sanded, and there is no special limitation on the sanding form, for example, a horizontal belt sander, a vertical belt sander, etc. can be selected.

[0030] Specifically, grooves are pressed on the surface of the polishing layer. There is no special limitation on the groove forming method, such as hot pressing mold forming, mechanical groove forming, etc. There is no special limitation on the groove shape, such as straight line, grid, spiral, etc.

[0031] Specifically, the polishing layer is connected to the middle support layer and the adhesive release layer in sequence through the adhesive layer, and the middle support layer material comprises a textile material or a non-woven material or a hard film material, such as a felt material impregnated with polyurethane, a textile material such as a thick flannel material, a hard film material such as a PET film, a PC film, etc. The adhesive release layer is preferably a double-sided adhesive material with a release paper.

[0032] Specifically, the polishing pad can be applied to the field of chemical mechanical polishing, including but not limited to chemical mechanical polishing of silicon wafers, SiC, sapphire, etc.

[0033] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0034] The main sources of raw materials used in the embodiments and comparative examples of the present invention are as follows:

[0035] Table 1. Sources of main raw materials in Examples and Comparative Examples

[0036] Raw material name factory MDI-100 Wanhua Chemical WHP-202 Wanhua Chemical WHP-204 Wanhua Chemical CMA-44 Huada Chemical CMA-2085 Huada Chemistry ODX-218 Huada Chemistry HDW-3050T Huada Chemistry N,N-Dimethylformamide Hualu Hengsheng

[0037] Unless otherwise specified, other raw materials or reagents were obtained from commercial sources.

[0038] Polishing test: using EBARAFREX300 polishing machine, CMC D3586 polishing liquid, Oxide (PETEOS), SaesolAG62 dresser, and 775 mm diameter polishing pad.

[0039] The polishing parameters are as follows: polishing pressure 1.7 psi, polishing speed TT / TR: 95 / 86 rpm, polishing liquid flow rate 300 mL / min, and polishing time 60 s.

[0040] Polishing rate RR (angstroms / minute) test: After chemical mechanical polishing of PETEOS, the thickness difference and mass difference before and after polishing are measured using a thickness gauge and a balance to evaluate the polishing rate;

[0041] Polyurethane resin 100% modulus test: According to the method in QB / T 4197-2011, prepare a tensile specimen with a length of 75 mm and a width of 25 mm, and use a tensile testing machine to perform a tensile test at a speed of 100±5 mm / min. The tensile force value at the elongation of 100% is used to calculate the 100% modulus value of the resin.

[0042] Polyurethane resin elongation at break test: According to the method in QB / T 4197-2011, prepare a tensile specimen with a length of 75 mm and a width of 25 mm, and use a tensile testing machine to perform a tensile test at a speed of 100±5 mm / min. The elongation at break of the specimen is calculated according to the distance difference between the scales before and after the specimen breaks.

[0043] Polishing layer density test: Cut 10cm×10cm of sanded polishing layer, measure the thickness of the polishing layer with a micrometer, weigh the polishing layer with a balance, calculate the density, and take the average value of the density of 3 specimens for each sample.

[0044] Polishing layer 40h average recovery rate test: Use a compression rate tester in a 50℃ constant temperature and humidity oven, set the pressure surface to 1cm, the initial load to 18g, and the test thickness after 30s of pressure is recorded as t 0, The final load is 180g, and the test thickness after 30s of pressurization is recorded as t 1, After 40 hours of pressurization, the final load is removed and the thickness after 30 seconds of testing is recorded as t2. The recovery rate (%) =

[0045] 100×(t2-t1) / (t0-t1).

[0046] Example 1

[0047] Preparation of polyurethane resin: 1050g DMF, 99g BDO, 1000g WHP-202, 4.2g antioxidant 1135, 2.4g stannous octoate were added into a reactor, the temperature was controlled at 70-80°C with stirring, MDI 100 was added in 5 portions (401g in total), the remaining DMF 2332g was added in 6 portions, and the viscosity of the tested resin reached 80000-10000cp. When the temperature was 25°C, 2g methanol was added, the material was stirred evenly and discharged, the tested resin had a 100% modulus of 4MPa and an elongation at break of 526%.

[0048] Preparation of polishing layer: 100 parts of the above-mentioned polyurethane resin, 3 parts of Span-83, and 50 parts of N,N-dimethylformamide are prepared into a polyurethane slurry, and the slurry is evenly coated on a PET film with a thickness of 1.4 mm using a coater, and then immersed in a 20°C, 10% DMF aqueous solution for curing for 50 minutes. After washing and drying, the surface is sanded with 180-mesh sandpaper using a vertical sand belt machine, and the removal amount is controlled to be 0.20 mm. A 130°C hot pressing mold is used to emboss a grid-type groove to obtain a polishing layer.

[0049] The polishing layer is then combined with the felt material impregnated with polyurethane, and then the backing adhesive is affixed, and a release layer is affixed to obtain a chemical mechanical polishing pad.

[0050] Example 2

[0051] Preparation of polyurethane resin: 1077g DMF, 82g EG, 1000g WHP-204, 11354.2g antioxidant, 2.4g stannous octoate were added into a reactor and the temperature was controlled at 70-80°C under stirring. MDI 100 (456g in total) was added in 5 portions, and the remaining DMF 2512g was added in 6 portions. When the viscosity of the test resin reached 80000-10000cp. at 25°C, 2g methanol was added, the material was stirred evenly and discharged. The test resin had a 100% modulus of 5MPa and an elongation at break of 560%.

[0052] Preparation of polishing layer: 100 parts of the above-mentioned polyurethane resin, 1 part of Tween 20, and 45 parts of N,N-dimethylformamide were prepared into a polyurethane slurry, and the slurry was evenly coated on a PET film with a thickness of 1.3 mm using a coater, and then immersed in a 23°C, 14% DMF aqueous solution for curing for 50 minutes. After washing and drying, the surface was sanded with 180-mesh sandpaper using a vertical sand belt machine, and the removal amount was controlled to be 0.20 mm. A 130°C hot pressing mold was used to emboss a grid-type groove to obtain a polishing layer.

[0053] The polishing layer is then combined with a PET film having a thickness of 0.188 mm, and then the backing adhesive is adhered, and a release layer is attached to obtain a chemical mechanical polishing pad.

[0054] Example 3

[0055] Preparation of polyurethane resin: 1147g DMF, 102g BDO, 1000g CMA-44, 4.2g antioxidant 1135, 2.4g stannous octoate were added into a reactor and the temperature was controlled at 70-80°C under stirring. MDI 100 (537g in total) was added in 5 portions, and the remaining DMF 2677g was added in 6 portions. When the viscosity of the tested resin reached 80000-10000cp. At 25°C, 2g methanol was added and the material was uniformly stirred and discharged. The tested resin had a 100% modulus of 8MPa and an elongation at break of 510%.

[0056] Preparation of polishing layer: 100 parts of the above-mentioned polyurethane resin, 2 parts of OP-7, and 50 parts of N,N-dimethylformamide were prepared into a polyurethane slurry, and the slurry was evenly coated on a PET film with a thickness of 1.5 mm using a coater, and then immersed in a 25°C, 15% DMF aqueous solution for curing for 50 minutes. After washing and drying, the surface was sanded with 180-mesh sandpaper using a vertical sand belt machine, and the removal amount was controlled at 0.20 mm. A 130°C hot pressing mold was used to emboss a grid-type groove to obtain a polishing layer.

[0057] The polishing layer is then combined with a PC film having a thickness of 0.188 mm, and then the backing adhesive is affixed, and a release layer is affixed to obtain a chemical mechanical polishing pad.

[0058] Example 4

[0059] Preparation of polyurethane resin: 1093g DMF, 102g EG, 510g WHP-202, 490g WHP-204, 4.2g antioxidant 1135, 2.4g stannous octoate were added into a reactor and the temperature was controlled at 70-80°C with stirring. MDI 100 (a total of 537g) was added in 5 portions, and the remaining DMF 2552g was added in 6 portions. When the viscosity of the test resin reached 80000-10000cp. at 25°C, 2g methanol was added, the material was uniformly stirred and discharged, and the test resin 100% modulus was 8.5MPa and the elongation at break was 570%.

[0060] Preparation of polishing layer: 100 parts of the above-mentioned polyurethane resin, 2 parts of polyethylene glycol (400) monostearate, and 65 parts of N,N-dimethylformamide are prepared into a polyurethane slurry, the slurry is evenly coated on a PET film with a thickness of 1.3 mm, immersed in a 21°C, 13% DMF aqueous solution for curing and molding for 50 minutes, after washing and drying, the surface is sanded with 180-mesh sandpaper using a vertical sand belt machine, and the removal amount is controlled at 0.20 mm. A 130°C hot pressing mold is used to emboss a grid-type groove to obtain a polishing layer.

[0061] The polishing layer is then combined with the felt material impregnated with polyurethane, and then the backing adhesive is affixed, and a release layer is affixed to obtain a chemical mechanical polishing pad.

[0062] Comparative Example 1

[0063] The same steps as in Example 1 were used to prepare a polyurethane resin.

[0064] The polishing layer was prepared by the same steps as in Example 1, except that the concentration of the coagulation bath was 6%.

[0065] The polishing layer is then combined with the felt material impregnated with polyurethane, and then the backing adhesive is affixed, and a release layer is affixed to obtain a chemical mechanical polishing pad.

[0066] Comparative Example 2

[0067] Preparation of polyurethane resin: 1000g DMF, 60g EG, 1000g WHP-204, 11354.2g antioxidant, 2.4g stannous octoate were added to a reactor and the temperature was controlled at 70-80°C with stirring. MDI 100 (368g in total) was added in 5 portions, and the remaining DMF 2333g was added in 6 portions. When the viscosity of the test resin reached 80000-10000cp. at 25°C, 2g methanol was added, the material was uniformly stirred and discharged, and the test resin 100% modulus was 3MPa and the elongation at break was 590%.

[0068] The same steps as in Example 2 were used to prepare the polishing layer.

[0069] The polishing layer is then combined with a PET film having a thickness of 0.188 mm, and then the backing adhesive is adhered, and a release layer is attached to obtain a chemical mechanical polishing pad.

[0070] Comparative Example 3

[0071] Preparation of polyurethane resin: 1093g DMF, 115.8g BDO, 100g CMA-44, 900g CMA-2085, 4.2g antioxidant 1135, 2.4g stannous octoate were added into a reactor and the temperature was controlled at 70-80°C under stirring. MDI 100 (447g in total) was added in 5 portions, and the remaining DMF 2552g was added in 6 portions. When the viscosity of the tested resin reached 80000-10000cp. At 25°C, 2g methanol was added and the material was uniformly stirred and discharged. The tested resin had a 100% modulus of 7MPa and an elongation at break of 380%.

[0072] The same steps as in Example 2 were used to prepare the polishing layer.

[0073] The polishing layer is then combined with a PET film having a thickness of 0.188 mm, and then the backing adhesive is adhered, and a release layer is attached to obtain a chemical mechanical polishing pad.

[0074] Comparative Example 4

[0075] Preparation of polyurethane resin: 1206g DMF, 158g BDO, 1000g ODX-218, 4.2g antioxidant 1135, 2.4g stannous octoate were added into a reactor, the temperature was controlled at 70-80°C with stirring, MDI 100 was added in 5 portions (a total of 565g), the remaining DMF 2814g was added in 6 portions, and the viscosity of the tested resin reached 80000-10000cp. When the temperature was 25°C, 2g methanol was added, the material was stirred evenly and discharged, and the 100% modulus of the tested resin was 11MPa and the elongation at break was 360%.

[0076] The same steps as in Example 2 were used to prepare the polishing layer.

[0077] The polishing layer is then combined with a PET film having a thickness of 0.188 mm, and then the backing adhesive is adhered, and a release layer is attached to obtain a chemical mechanical polishing pad.

[0078] Comparative Example 5

[0079] The polishing layer was prepared by the same steps as in Example 3, except that the resin HDW-3050T was used (the test resin had a 100% modulus of 6 MPa and an elongation at break of 800%).

[0080] The polishing layer is then combined with a PC film having a thickness of 0.188 mm, and then the backing adhesive is affixed, and a release layer is affixed to obtain a chemical mechanical polishing pad.

[0081] The test results of the density and 40h average recovery rate of the polishing layer prepared in the embodiment and the comparative example are shown in Table 2.

[0082] Table 2. Polishing layer density and 40h average recovery rate test results

[0083]

[0084] The polishing pads prepared in the examples and comparative examples were subjected to polishing tests to obtain the removal rates. The test results are shown in FIG. Figure 1 shown.

[0085] pass Figure 1 The test results show that the polishing pad prepared by the present invention can maintain the stability of the polishing rate and effectively extend the service life.

[0086] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A soft porous foam polishing layer, characterized in that: The density of the polishing layer is greater than or equal to 0.20 g / cm 3 , less than or equal to 0.23g / cm 3 , and the recovery rate is >90% at 50℃ and 18KPa for 40 hours.

2. The porous foam polishing layer according to claim 1, characterized in that: The material of the polishing layer is a mixture of one or more of polyurethane resin and polyvinyl chloride resin, preferably polyurethane resin.

3. The porous foam polishing layer according to claim 2, characterized in that: The 100% modulus of the polyurethane resin is 4 to 9 MPa, preferably 5 to 8 MPa.

4. The porous foam polishing layer according to any one of claims 1 to 3, characterized in that: The elongation at break of the polyurethane resin is 400-700%, preferably 500-600%.

5. The porous foam polishing layer according to any one of claims 1 to 4, characterized in that: The polishing layer has a recovery rate of >95% at 50° C. and 18 KPa for 40 hours.

6. The porous foam polishing layer according to any one of claims 1 to 5, characterized in that: The polishing layer is prepared by a non-solvent phase conversion method.

7. The porous foam polishing layer according to claim 6, characterized in that: The method for non-solvent phase conversion comprises the following steps: i) preparing a uniform coating slurry with resin, additives and solvent; ii) uniformly coating the coating slurry on the support layer and curing and forming the coating slurry in a coagulation bath; iii) Wash and dry.

8. A chemical mechanical polishing pad, characterized in that: The soft porous foam polishing layer comprises the polishing layer as claimed in any one of claims 1 to 7, wherein the polishing layer is subjected to surface sanding and groove pressing, and is connected with the middle support layer and the back adhesive release layer in sequence through the adhesive layer.

9. The chemical mechanical polishing pad according to claim 8, characterized in that The intermediate support layer material includes any one of a textile material, a non-woven material, and a hard film material; the adhesive release layer is a double-sided adhesive material with release paper.

10. Use of the chemical mechanical polishing pad according to claim 8 or 9 in chemical mechanical polishing.

Citation Information

Patent Citations

  • Multi-structure chemical mechanical polishing pad, and manufacturing method and application thereof

    CN112757153A

  • Polishing pad employing polyamine and cyclohexanedimethanol curing agents

    CN114450127A

  • Preparation method of buffer layer of chemical mechanical polishing pad, buffer layer, polishing pad containing buffer layer and application

    CN116787323A

  • Chemical mechanical polishing pad with two types of sponge holes as well as preparation method and application of chemical mechanical polishing pad

    CN118769125A

  • Polishing pad

    JP2010069551A

Cited By

  • Polishing pad and preparation method thereof

    CN121156908A